(untitled) (Research, Society and Development, 2022)
Objective: In view of the construction of public health policies in Brazil, focusing on neglected populations, it is known that the care of the homeless population is still in the infancy. In this sense, this article describes the sociodemographic and epidemiological profile of the homeless population assisted by the Recife Street Clinic. Methods: A quantitative cross-sectional descriptive study and a sample of 94 homeless people, using a questionnaire developed by the researchers. For the analysis of continuous numerical variables, measures of central tendency and their dispersions and Pearson’s chi-square test with significance of p-value < 0.05 for categorical variables were used. Results: Most of the sample consisted of men (61.7%) and of mixed race (59.6%). Approximately half (41.5%) of the interviewees indicated that family disagreements are the main reason for being on the street, in addition to a tendency to perpetuate the homeless situation, given the percentage of 35.1% having been in this situation for more than 10 years. A preference was identified for overnight stays on the streets (88.3%), as well as a percentage of 85.1% reporting some morbidity. Conclusion: This study highlights the need to implement public policies through a more fair and equitable approach for the population in question.